2020
DOI: 10.1080/10872981.2019.1710324
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions of online and in-person microbiology laboratory experiences in undergraduate medical education

Abstract: Background: Universities are facing increased budget constraints, often resulting in reduced funds to support microbiology laboratories. Online mock laboratory activities are often instituted as a cost-effective alternative to traditional wet labs for medical students. Objective: The purpose of this study was to examine students' perceptions of online and inperson microbiology lab learning experiences. Design: We investigated undergraduate medical student perception of the in-person and online microbiology lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 30 publications
9
68
1
5
Order By: Relevance
“…23 While a third study from USA illustrated that the majority of medical students preferred the blinded learning methods consisting of both online and in-person laboratory practice for their microbiology laboratory course. 24 The current study revealed that most students reported that they do not need a computer skill literacy courses and they can use the online learning platforms for communicating effectively with instructors and other students without difficulties. Among the challenges that the participant of the current study students agreed on were lack of the motivation, feeling board during an online class, and that some of them took them long time to adapt to online learning tools.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…23 While a third study from USA illustrated that the majority of medical students preferred the blinded learning methods consisting of both online and in-person laboratory practice for their microbiology laboratory course. 24 The current study revealed that most students reported that they do not need a computer skill literacy courses and they can use the online learning platforms for communicating effectively with instructors and other students without difficulties. Among the challenges that the participant of the current study students agreed on were lack of the motivation, feeling board during an online class, and that some of them took them long time to adapt to online learning tools.…”
Section: Discussionmentioning
confidence: 73%
“… 23 While a third study from USA illustrated that the majority of medical students preferred the blinded learning methods consisting of both online and in-person laboratory practice for their microbiology laboratory course. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Kryzhanovskaya et al (2018) investigated the methodological approaches to delivering lectures on MBVI at medical universities, the features of this course and ways to improve it for international students. Hamorak (2015), Ngamskulrungroj et al (2017), and Brockman et al (2020) presented their experience of teaching MBVI with the use of interactive and distance learning technologies.…”
Section: Introductionmentioning
confidence: 99%
“…We chose a format of a virtual moderated podium discussion with questions from the audience. An in-person format was evaluated positively in the past and seemed suitable for our learning objectives [ 8 ], [ 9 ], [ 10 ]. We sought to use this successful in-person format for an online event.…”
Section: Project Descriptionmentioning
confidence: 99%